2008
DOI: 10.1080/03093640802016639
|View full text |Cite
|
Sign up to set email alerts
|

Functional gait analysis of trans-femoral amputees using two different single-axis prosthetic knees with hydraulic swing-phase control

Abstract: This paper reports a comparison of the gait patterns of trans-femoral amputees using a single-axis prosthetic knee that coordinates ankle and knee flexions (Proteor's Hydracadence system) with the gait patterns of patients using other knee joints without a knee-ankle link and the gait patterns of individuals with normal gait. The two patient groups were composed of 11 male trans-femoral amputees: six patients had the Hydracadence joint (Group 1) and five patients had other prosthetic knees (Group 2). The refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 6 publications
2
11
0
1
Order By: Relevance
“…Typically, quantitative assessments of prostheses performances rely on spatio-temporal, kinematic and kinetic gait characteristics [1][2][3][4][5][6]. In particular, the analysis of lower limb joints kinetics (i.e., forces, moments, power) has become critical to compare mechanical performances between adaptive dissipation prosthetic knee units [7][8][9][10][11][12][13][14][15][16][17][18][19] and an anatomical knee joint [2,3,20]. Furthermore, the development of osseointegrated fixations for bone-anchored prostheses requires a better understanding and monitoring of implant and prosthetic loading during locomotion to increase walking abilities (e.g., speed of walking) while assuring safety (e.g., limitation of high loading, fall prevention, breakage of fixation parts) [6,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, quantitative assessments of prostheses performances rely on spatio-temporal, kinematic and kinetic gait characteristics [1][2][3][4][5][6]. In particular, the analysis of lower limb joints kinetics (i.e., forces, moments, power) has become critical to compare mechanical performances between adaptive dissipation prosthetic knee units [7][8][9][10][11][12][13][14][15][16][17][18][19] and an anatomical knee joint [2,3,20]. Furthermore, the development of osseointegrated fixations for bone-anchored prostheses requires a better understanding and monitoring of implant and prosthetic loading during locomotion to increase walking abilities (e.g., speed of walking) while assuring safety (e.g., limitation of high loading, fall prevention, breakage of fixation parts) [6,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al [76] use a three-dimensional biomechanical model to determine upper extremity kinematics of 16 male subjects with low-level paraplegia while performing wheelchair propulsion. Sapin et al [78] report a comparison of the gait patterns of transfemoral amputees using a singleaxis prosthetic knee that coordinates ankle and knee flexions (Proteor's Hydracadence system) with the gait patterns of patients using other knee joints without a knee-ankle link and the gait patterns of individuals with normal gait. In [75], spatiotemporal, kinematics, kinetics, and EMG data as well as the physiological changes associated with gait and ageing are reviewed, in order for the authors to provide gait analysis regarding older people.…”
Section: Physical Modellingmentioning
confidence: 99%
“…Sapin et al (2008) [ 25] reported a comparison of the gait patterns of trans-femoral amputees using a single-axis prosthetic knee that coordinates ankle and knee flexion's with the gait patterns of patients using other knee joints without a knee-ankle link and the gait patterns of individuals with normal gait. Prince et al (1997) [ 26], reviewed spatio-temporal, kinematics, kinetics and EMG data as well as the physiological changes associated with gait and aging.…”
Section: Virtual Human Modellingmentioning
confidence: 99%